Folhetos de cordel no ensino de física : um estudo de caso em escolas dos municípios de Paulo Ramos e São Luís Gonzaga do Maranhão - Silva, André Flávio Gonçalves (2023)
The teaching of physics, despite its significant advances, there is still a problem pointed out by Charles Percy Snow in 1950, who already reported that it was a problem from at least 50 years ago: scientific culture does not dialogue with humanistic culture, which entails damage to humanity as a whole and each culture remains dialoguing and producing in isolation. The cordel booklets, which have always had an educational function, mainly in the Brazilian northeast, and which use local knowledge to dialogue with their audience, this research sought to make notes about how the relationship between physics teaching occurs with cordel booklets in schools in the rural region of Maranhão. To develop a teaching sequence for the use of cordel booklets in Physics Teaching, mainly, for the alternation pedagogy regime and an analysis based on the intervention in schools in the rural region of Maranhão. The elaboration of the teaching sequence was based on the sequence developed by the teacher and researcher Augusto Nobre and the Theory of Critical Meaningful Learning. After preparing the sequence, a 10-hour pilot project was applied in three schools, two in the city of Paulo Ramos and another in São Luís Gonzaga, Maranhão, divided into students and teachers. Finally, it was possible to perceive that some stages of the developed didactic sequence end up coexisting in a natural way. Concern was also evident in the acquisition of leaflets for use and acceptance of the proposal was determined by knowledge of the leaflets and surprise in using them for Science Teaching. In view of the elaboration and application, there is a need for future research to fill the gap that deals with cordel booklets in Science Teaching, more specifically, in Physics Teaching in schools in/in the countryside and that work with Pedagogy of Alternation.